2012
DOI: 10.1080/07325223.2013.730020
|View full text |Cite
|
Sign up to set email alerts
|

Supervisors' Use of Reinforcement, Reframing, and Advice to Re-Author the Supervisory Narrative through E-mail Supervision

Abstract: Discourse analysis was used to investigate the semester-long weekly e-mail communication between 38 counseling supervisees in their internship placements across school, clinical mental health, and student affairs placement settings and their three respective supervisors. Evidence of supervisor re-authorship of the supervisory narrative-the stories that constitute supervisory communication and shape the interpretation of experiences-was found throughout the e-mail communication in the forms of reinforcement and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…These positive clinical benefits appear to translate into the supervisory relationship as well. Luke and Gordon (2012) found that clinical supervision by e-mail helped clients reflect on and reframe their clinical experiences. Letter-writing enabled one of my counselor trainees to express her struggle with issues of competence and performance anxiety when working with her adolescent client (the letter was not actually given to the client; it was used as a supervisory technique only).…”
Section: Conceptualizationmentioning
confidence: 97%
“…These positive clinical benefits appear to translate into the supervisory relationship as well. Luke and Gordon (2012) found that clinical supervision by e-mail helped clients reflect on and reframe their clinical experiences. Letter-writing enabled one of my counselor trainees to express her struggle with issues of competence and performance anxiety when working with her adolescent client (the letter was not actually given to the client; it was used as a supervisory technique only).…”
Section: Conceptualizationmentioning
confidence: 97%
“…Furthermore, discussions can be held about how to work within the context of the current political system, so that they and their allies (potentially including their counselor) can work for more long-term and systemic change. This process typically begins when forming intentional relationships, but these relationships are not in a vacuum; rather using a systemic understanding, Wenger (1998) and others (Luke & Gordon, 2011, 2012) have recognized that the collaborative relationships are more than interpersonal, and they create something larger, namely a community of practice. The concept of a counseling community of practice can be extended into an educational context as well, wherein social justice scholars (Bemak, 2005; Goodrich & Luke, 2015; Kolb, 1984) regularly employ humanistic pedagogy, including experiential and reflective learning, in effort to achieve many of the advocacy tenets seen in queer theory.…”
Section: Social Justice Applications Of Queer Theory In Humanistic Comentioning
confidence: 99%
“…In fact, Chapman, Baker, Nassar-McMillan, and Gerler’s (2011) case-study analysis of one semester-long supervision course uncovers comparable success between face-to-face and online supervision; effectiveness of e-mail supervision, however, nevertheless remains understudied (e.g., as noted by Clingerman & Bernard, 2004). The discourse of e-mail supervision, including how linguistic features might facilitate the professional identity development process, is also understudied (but see Gordon & Luke, 2012, 2013; Luke & Gordon 2011, 2012). Thus, our investigation aims to fill a gap in the discourse analysis and counseling and supervision literatures.…”
Section: Supervision and Professional Training For Counselorsmentioning
confidence: 99%
“…However, later in the message, the intern also displays her novice professional identity related to this event: She closes by stating, “Other than talking about the services that [local service name] offers for abused women, I am not sure what else I can do to provide help for [client’s name]. Any thoughts that you have would be appreciated, Beatrix.” She thus asks for advice; while she is able to competently enact the counseling role in some situations, she is still a relative novice (see Gordon & Luke, 2013; Luke & Gordon, 2012 for more on advice in e-mail supervision).…”
Section: Uses Of “We” By Institutional Rolementioning
confidence: 99%